Addressing critical needs in the fight to end tuberculosis with innovative tools and strategies - Hatherill, Mark; Chaisson, Richard E.; Denkinger, Claudia M. (PLoS medicine, 2019)
This month in PLOS Medicine we launched a Special Issue on New Tools and Strategies for Tuberculosis Diagnosis, Care, and Elimination. In this issue’s Editorial, the Guest Editors Claudia Denkinger, Richard Chaisson, and Mark Hatherill highlight some of the research that will publish and how these studies focusing on discovery, clinical trials and implementation research collectively add to the prospects for reaching the EndTB targets of the WHO by 2035.
Gesehen am 26.03.2020